A larger pie or a larger slice? Contract negotiation in a closed-loop supply chain with remanufacturing. (April 2020) - Huang, He; Xiong, Yu; Zhou, Yu
Highlights: The impact of remanufacturing on supply chain coordination is investigated. The upstream player always prefers a two-part tariff that coordinates the supply chain. Without remanufacturing, the downstream player prefers a wholesale-price contract. With remanufacturing, the downstream player prefers a two-part tariff under certain conditions. Remanufacturing facilitates the use of sophisticated contracts to coordinate the supply chain. Abstract: The common wisdom is that remanufacturing complicates supply chain management, and hence prevents supply chain coordination. In this paper, we demonstrate that remanufacturing could facilitate supply chain coordination. The impact of remanufacturing on supply chain coordination is investigated by examining the firms' preferred contractual form when they negotiate to reach an agreement. From a downstream perspective, a two-part tariff generates a higher channel profit (a larger pie) since it coordinates the supply chain; while a wholesale-price contract yields a larger slice of the pie because it comes with a quantity flexibility and forces the upstream firm to forbear the use of bargaining power. In a supply chain without remanufacturing, the upstream firm always prefers the two-part tariff, and the downstream firm always prefers the wholesale-price contract. However, in a closed-loop supply chain with remanufacturing, the downstream firm's preference may be reversed in that the value of the quantity flexibility shrinks when the remanufactured product quantity is bounded by the new product quantity. Hence, the development of remanufacturing might facilitate the use of a sophisticated contract to coordinate the supply chain.